2019
DOI: 10.18805/ijare.a-337
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ perceptions of drought and other production constraints, drought mitigation options, and their implications for groundnut breeding in Uganda

Abstract: A participatory rural appraisal was conducted in selected groundnut growing areas of Uganda to determine how smallholder farmers perceive and cope with drought, identify farmers’ constraints, and study the production systems, and varietal preferences in groundnut production. Majority of farmers surveyed, agreed that drought is a major production constraint. The local drought perceptions were described by farmers (55.7%) as warm/hot windy conditions in eastern (55.7%), while in the northern region, little rainf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…The reaction of groundnut varieties to pests and diseases didn't signi cantly differ between landraces and improved varieties, even though incidence of pests and diseases was lower on improved varieties. These results corroborate those of Kakeeto et al (2018) where farmers selected improved varieties over landraces for their pest and disease resistance. However, these results contradict those of Aina et al (2011) who reported that landraces had better tolerance to CMD and CBB diseases compared to improved varieties of cassava.…”
Section: Comparison Of Growth Parameters Of Selected Improved Varieties and Landracessupporting
confidence: 85%
“…The reaction of groundnut varieties to pests and diseases didn't signi cantly differ between landraces and improved varieties, even though incidence of pests and diseases was lower on improved varieties. These results corroborate those of Kakeeto et al (2018) where farmers selected improved varieties over landraces for their pest and disease resistance. However, these results contradict those of Aina et al (2011) who reported that landraces had better tolerance to CMD and CBB diseases compared to improved varieties of cassava.…”
Section: Comparison Of Growth Parameters Of Selected Improved Varieties and Landracessupporting
confidence: 85%